Determinants of Nutritional Status of Adolescents Age 12-16 Years - nasution, ade saputra; Nuraida, Ida; Raharsari, Rezeki Tri; Putri, Devia Lydia; Suhenda, Dadang (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2023)
Adolescents really need high nutrients for growth and development, but most teenagers do not understand and consider nutritional intake according to their needs, this will have an impact on nutritional status and will even have an impact on health such as over nutrition and undernutrition, where This problem also results in a decrease in intelligence, weakening of the immune system and even triggers the emergence of various types of degenerative diseases. The problem of nutritional status consists of multi-factors such as nutritional knowledge, food availability, eating habits, exercise, and other factors. Analyzing any determinants related to the nutritional status of adolescents. The type of observational analytic with a cross-sectional design was used as a research design, the sample was 57 teenagers who were taken using a random sampling technique, the data obtained were analyzed using the chi-square test. The nutritional knowledge variable has a value of 0.025 which means it has a relationship with nutritional status, exercise habits have a relationship with adolescent nutritional status with a value of 0.005, eating habits have no relationship with adolescent nutritional status with a value of 0.893 and food availability has no relationship with nutritional status with a value of 0.893. 0.491. The variables of nutritional knowledge and exercise habits have more influence on the nutritional status of adolescents than the variables of food availability and eating habits of adolescents.